(untitled) (Medico Legal Update, 2021)
Background: White roll vermillion turn down flap is a modification on Millard’s technique of rotation – advancement repair for unilateral primary cleft lip deformity. Aim of Study: This research to evaluate a new modification on Millard’s technique of primary unilateral chieloplasty. Patients and Methods: A prospective study was done and involved 20 patients were surgically treated by Meshra’s technique of white roll vermillion turn down flap at Al-Shaheed Ghazii Alharriri and Al-Wasty hospital between April 2015 to April 2017. 12 male versus 8 female presented to us with unilateral cleft lip there ages were ranging between 3 months to 30 months, these patients surgically treated by white roll vermillion turn down flap. Results: A prospective study was involved of 20 cases of primary cleft lip repair with this technique, we have achieved 17 cases with a good symmetry and peaking of cupids bow with no vermillion notching of the lips and without major complications. Conclusion: White roll vermillion turn down flap gave us a good look of the cleft patient and satisfactory for his family. It’s applicable and takes same time for Millard’s technique.